2003
DOI: 10.1128/aem.69.6.3077-3084.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxigenic Fusarium and Deoxynivalenol Production Repress Chitinase Gene Expression in the Biocontrol Agent Trichoderma atroviride P1

Abstract: Mycotoxin contamination associated with head blight of wheat and other grains caused by Fusarium culmorum and F. graminearum is a chronic threat to crop, human, and animal health throughout the world. One of the most important toxins in terms of human exposure is deoxynivalenol (DON) (formerly called vomitoxin), an inhibitor of protein synthesis with a broad spectrum of toxigenicity against animals. Certain Fusarium toxins have additional antimicrobial activity, and the phytotoxin fusaric acid has recently bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
78
1
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 55 publications
1
78
1
5
Order By: Relevance
“…For instance, it is possible to discern patterns of gene induction and to observe fungal interactions in vivo that occur in the soil and around the plant (36). This methodology may provide a way to monitor biocontrol activity (20) and the plant-Trichoderma interaction, thereby improving the selection of useful strains and the effectiveness of biopesticide and biofertilizer treatments.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it is possible to discern patterns of gene induction and to observe fungal interactions in vivo that occur in the soil and around the plant (36). This methodology may provide a way to monitor biocontrol activity (20) and the plant-Trichoderma interaction, thereby improving the selection of useful strains and the effectiveness of biopesticide and biofertilizer treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Their study showed that the mycotoxin deoxynivalenol produced by Fusarium culmorum and Fusarium graminearum acts as a negative signal repressing the expression of the nag1 chitinase gene in Trichoderma atroviridae. Repression appeared to be specific for nag1 since no adverse effect was observed on the expression of ech42, another important chitinase gene in T. atroviridae (Lutz et al 2003).…”
Section: Interference With the Biosynthesis Of Antimicrobial Compoundmentioning
confidence: 99%
“…Another example of pathogen-antagonist signalling was described for the interaction between mycotoxigenic Fusarium and mycoparasitic Trichoderma (Lutz et al 2003). Their study showed that the mycotoxin deoxynivalenol produced by Fusarium culmorum and Fusarium graminearum acts as a negative signal repressing the expression of the nag1 chitinase gene in Trichoderma atroviridae.…”
Section: Interference With the Biosynthesis Of Antimicrobial Compoundmentioning
confidence: 99%
“…Mycotoxins produced by Fusarium spp., including fusaric acid, typically have broad-spectrum antibiotic activity affecting bacteria, fungi, nematodes, insects, and mammals (39, 67), and their activity can be synergistic (13). An unexpectedly diverse range of Fusarium species have been found to produce fusaric acid and other mycotoxins in environments that require aggressive saprophytic competition with other organisms (i.e., grain [2] and crop residues [36]). The potential ecological importance of mycotoxins with respect to the saprophytic life cycles of producing fungi is largely unknown, although inhibition of bacteria and other microbial competitors or animal consumers of crop residues may enhance the saprophytic survival of plant-infectious mycotoxigenic Fusarium in crops.…”
mentioning
confidence: 99%